Spatial Analysis of National Food Production Vulnerability to Soil Quality Degradation: Correlating Soil Organic Carbon Levels and Rice Productivity Based on BBSDLP Data - Munawarah; Ibrohim (Agriculture Journal, 2024)
The stagnation of national rice productivity in Indonesia, often termed a “productivity plateau,” poses a serious risk to long-term food security. This study examines the vulnerability of rice production by analyzing the relationship between Soil Organic Carbon (SOC) levels and regional productivity using secondary data from BBSDLP and the Central Bureau of Statistics (BPS). Spatial analysis covering 7.46 million hectares of Lahan Baku Sawah indicates that 68.45% of intensive paddy fields exhibit soil fatigue, with SOC levels below the critical threshold of 1.5%. Statistical results reveal a strong positive correlation between SOC and rice yields (r = 0.74, p < .001). Regression analysis shows that SOC variation explains 54.7% of productivity fluctuations, demonstrating that mineral fertilizer effectiveness is constrained by organic matter depletion. High Vulnerability Red Zones are concentrated in technically irrigated areas of Java, where intensive cropping without organic restitution has degraded soil structure. These findings underscore the need to shift agricultural policy from mineral-based subsidies toward an integrated soil health strategy centered on organic carbon restoration as a prerequisite for sustainable food production.